Legal Protection Against Insults on Social Media as a Form of Cyberbullying: Case Study of Decision Number: 21/Pid.Sus/2020/PN.Lbo - Zahrah, Mutiara; Alhadi, Muhammad Nurcholis; Prasetyo, Bayu (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The phenomenon of insults on social media as a form of Cyberbullying or bullying in cyberspace is an act of intimidation, humiliation, humiliation, or deliberate harassment through the internet, focusing on the case study of Decision Number: 21/Pid.Sus/2020/PN.lbo. The main issues raised are the legal protection of victims of cyberbullying and the effectiveness of law enforcement in Indonesia.Purposes of the Research: To identify the protection mechanisms available to victims and assess the extent to which the law can be enforced against the perpetrators of cyberbullying.Methods of the Research: The research method used is normative juridical, with a legislative approach and case studies. Data were collected through a review of the literature, including relevant Laws and the results of previous research.Findings of the Research: Showing that in the Cyberbullying case at the Lamboto District Court, the defendant was sentenced in accordance with the Electronic Information and Transaction Law for defamation on social media. This decision emphasizes justice, legal fairness, and protection for victims and provides a deterrent effect for perpetrators while showing that the Judge's commitment to providing justice in the judiciary in handling crimes in cyberspace.